Analysis of Competitive Advantage and Its Relevance to SME Sustainability: A Case of Nigerian Manufacturing Industry - OGBARI, Mercy Ejovwokeoghene; KEHINDE, Busola E; OGULU, Belema Stephanie (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose: The study examined competitive advantage and its relevance to SME sustainability using selected manufacturing companies in Lagos, Nigeria. The study's objectives were to determine the impact of innovation on product quality sales volume, among others of SMEs. The study was developed around resource and market-based theories.Methodology:The survey descriptive research design was adopted, and data were obtained from questionnaires filled out by respondents from the selected manufacturing firms. Multiple Regression was adopted to test the hypotheses at a 0.05 significance level. The study revealed a positive effect between the selected variables.Findings: Based on the findings, it was recommended that employees be motivated to use personal skills and abilities in executing daily activities, encourage creative thinking, and generate new and innovative techniques to boost the quick achievement of organizational growth.Implication:This study was conducted to determine the relevance of competitive advantage to business sustainability. It was discovered that competitive advantage has relevance to the sustainability of businesses, innovation increases sales volume, product quality influences market share, and product price positively affects the returns on investment of the business.